Personal characteristics and transmission dynamics associated with SARS-CoV-2 semi-quantitative PCR test results: an observational study from Belgium, 2021–2022 - Braeye, Toon; Proesmans, Kristiaan; Van Cauteren, Dieter; Brondeel, Ruben; Hens, Niel; Vermeiren, Elias; Hammami, Naïma; Rosas, Angel; Taame, Adrae; André, Emmanuel; Cuypers, Lize (Frontiers in Public Health, 2024)
After harmonization efforts by the Belgian national reference center for SARS-CoV-2, semiquantitative PCR test (SQ-PCR) results, a proxy for viral load, were routinely collected after performing RT-qPCR tests. We investigated both personal characteristics associated with SQ-PCR results and the transmission dynamics involving SQ-PCR results.We used person-level laboratory test data and contact tracing data collected from March 2021 to February 2022 in Belgium. Personal characteristics (age, sex, vaccination and laboratory-confirmed prior infection) and disease stage by date of symptom-onset were fitted to SQ-PCR results using logistic regression. Vaccine effectiveness (VE) against high (>=10 7 copies/ml) viral load was estimated from the adjusted probabilities. Contact tracing involved the mandatory testing of High-Risk Exposure Contacts (HREC) after contact with an index case. Odds ratios for test positivity and high viral load of HREC by the SQ-PCR result of the index case were obtained from logistic regression models adjusting for age, sex, immunity status (vaccination, laboratory-confirmed prior infection), variant (Alpha, Delta, Omicron), calendar time and contact tracing covariates.We included 909,157 SQ-PCR results of COVID19 cases and 379,640 PCR and 72,052 SQ-PCR results of HREC. High viral load was observed more frequently among recent cases, symptomatic cases, cases over 25 years of age and in those not recently (<90 days) vaccinated. Primary schedule VE in the first 30 days after vaccination was estimated at 47.3% (95%CI 40.8-53.2, Delta-period). High viral load in index cases was associated with increased test positivity of HREC (OR 2.7, 95%CI 2.62-2.79) and among those testing positive, increased presence of high viral load (OR 2.84,).